Reading Comprehension Skills of Scientific Texts with Natural Sciences Content of Junior High School (SMP) Students in Magelang City - Sari, Kurnia Intan; Siswanto, Siswanto; Ismawati, Riva; Muhlisin, Ahmad (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Indraprasta PGRI, 2024)
The study analyzes the achievement of reading comprehension skills of scientific texts with IPA content of junior high school (SMP) students in Magelang City. The study is a quantitative study using a survey approach method. It is conducted in four SMPs in Magelang City. The study population is 8th grade junior high school (SMP) students in Magelang City that consists of 95 students. Data are generated through an objective test on the students. The analysis results indicate that the average reading comprehension skills of the SMP students in Magelang City is in the fair criteria with an average score of 65. In the literal level comprehension, the average score is 71, the inferential level comprehension receives an average score of 65, and the critical level comprehension, the average score is 58; therefore, all comprehension levels are in the fair category. Factors affecting the reading comprehension skills of the SMP students in Magelang City include environmental and psychological factors.